Performance drivers in the hospitality industry - Božič, Valentina (Mednarodno inovativno poslovanje, 2025)
Purpose of the article –The aim of this paper is to identify key elements that drive performance in the field of hospitality and to test their impact on performance on the sample of hospitality companies in Slovenia and Croatia.Research methodology –Extensive literature review and content analysis contributed to the list of 30 drivers of hospitality performance that have been evaluated through Delphi method. In quantitative study, final list of drivers is linked to performance data on the sample of hospitality companies from Slovenia and Croatia. Findings –Hotel managers evaluated service quality, segmentation, and customer satisfaction as the major performance drivers. Further analysis showed that there is no single driver of performance that is relevant for any hospitality company. Cluster analysis offered five groups of companies that focused on their specific mix of performance drivers. Practical implications –The research offers a holistic view on the field of performance drivers while offering guidelines for industry practitioners when deciding where to focus to achieve targeted performance.
Keywords: dejavniki uspešnosti; hotel performance; Hotelirstvo; performance drivers; resource-based theory; Strateško načrtovanje; teorija virov; uspešnost hotelov